(untitled) (Research, Society and Development, 2020)
This article aims to report the manifestation of psychological resilience processes in children, with emphasis on the factors that favour them, in different theoretical perspectives. To this end, a qualitative bibliographic research was carried out, based on a narrative review of the literature, which includes the presentation of some of the main theoretical approaches to the theme. It has come to the understanding that psychological resilience manifests itself as a dynamic, interactive, integral and bidirectional process that acts in the face of adverse conditions experienced by the individual, which may or may not be sufficient as a protective factor against psychological damage. It is concluded that the bases for the potential manifestation of psychological resilience are built, primarily, in childhood. One of the factors that favour the manifestation of child resilience processes is positive parenting practices, as these are responsible for contributing to children’s emotional and behavioural regulation ability, as well as for the formation of a positive and coherent sense about themselves. The quality of early interactions between the child and their primary caregivers is fundamental for the performance of intersubjective processes that are essential for a solid and flexible structuring of the ego.